Core-shell structure porous cellulose bead composite comprising additives and coating agents and method for manufacturing same
Patent Information
- Application Number
- KR1020250048164
- Authority / Receiving Office
- KR · KR
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-04-14
- Publication Date
- 2026-10-21
Smart Images

Figure PAT00001_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a porous cellulose bead composite having a core-shell structure comprising an additive and a coating agent, and a method for manufacturing the same. Background Technology
[0002] With advancements in materials science and technology, micro beads have gained value in industrial processes due to their cost-effectiveness, ease of production, and diverse applications. These fine spherical particles, typically ranging in diameter from several micrometers to several millimeters, are essential for various applications as they offer a wide range of surface-to-volume ratios. Due to the unique characteristics of micro beads—such as their size, surface area, and the ability to be processed with customized surface chemistry—they are used in various fields, including the cosmetics industry, biomedicine, and environmental science.
[0003] However, despite these extensive uses, the traditional production methods of synthetic microbeads, often derived from non-renewable petroleum-based polymers, have caused serious environmental problems. Sustainability to ecosystems and the potential for ecological damage have become urgent issues; therefore, research is needed on microbeads with enhanced stability and efficacy using eco-friendly alternatives such as biodegradable and renewable materials. The problem to be solved
[0004] The object of the present invention is to provide an environmentally friendly porous cellulose bead composite with a core-shell structure using cellulose and a method for manufacturing the same.
[0005] In addition, the objective of the present invention is to provide a porous cellulose bead composite having a core-shell structure comprising a bioactive substance and chitosan, and a method for manufacturing the same.
[0006] In addition, the objective of the present invention is to provide a porous cellulose bead composite with a core-shell structure that improves drug stability and sustained drug release performance, and a method for manufacturing the same. means of solving the problem
[0007] According to one aspect of the present invention, a cellulose bead composite is provided comprising: a core comprising a porous cellulose bead having pores and a bioactive substance supported on the porous cellulose bead; and a shell comprising chitosan coated on the core.
[0008] In addition, the size of the porous cellulose beads may be 1 to 50 μm, preferably 3 to 10 μm.
[0009] In addition, the specific surface area of the porous cellulose beads is 5 to 100 m² 2 / g, preferably 10 to 40 m 2 It can be / g.
[0010] In addition, the specific pore volume of the porous cellulose beads is 0.05 to 1.00 cm 3 / g, preferably 0.1 to 0.50 cm 3 It can be / g.
[0011] In addition, the above-mentioned bioactive substance may include one or more selected from the group consisting of vitamin C, vitamin A, vitamin E, niacinamide, salicylic acid, kojic acid, alpha-lipoic acid, ellagic acid, resveratrol, docohexaenoic acid (DHA), eicosapentaenoic acid (EPA), linoleic acid (LA), glutathione, caffeine, tranexamic acid, azelaic acid, and hyaluronic acid.
[0012] In addition, the above-mentioned bioactive substance may be supported on one or more selected from the group consisting of the surface of the porous cellulose and the pores of the porous cellulose.
[0013] In addition, the chitosan may include chitosan nanowhiskers.
[0014] In addition, the cellulose bead complex can release the bioactive substance to the outside of the cellulose bead complex over time.
[0015] According to another aspect of the present invention, a method for manufacturing a cellulose bead composite is provided, comprising: (a) reacting a first mixed solution comprising porous cellulose beads having pores and a bioactive substance to produce a core comprising said bioactive substance and a bioactive substance supported on said porous cellulose beads; and (b) reacting the core with a second mixed solution comprising chitosan to form a shell comprising chitosan coated on said core.
[0016] Additionally, the above step (a) may include: (a-1) a step of preparing a first mixed solution comprising porous cellulose beads having pores and a bioactive substance; and (a-2) a step of reacting the first mixed solution to prepare a core comprising the bioactive substance and the bioactive substance supported on the porous cellulose beads.
[0017] In addition, the first mixed solution of step (a-2) can be reacted at a pH of 1.5 to 2.5.
[0018] In addition, the above-mentioned bioactive substance may include one or more selected from the group consisting of vitamin C, vitamin A, vitamin E, niacinamide, salicylic acid, kojic acid, alpha-lipoic acid, ellagic acid, resveratrol, docohexaenoic acid (DHA), eicosapentaenoic acid (EPA), linoleic acid (LA), glutathione, caffeine, tranexamic acid, azelaic acid, and hyaluronic acid.
[0019] Additionally, the above step (b) may include (b-1) a step of preparing a second mixed solution containing the core and chitosan; and (b-2) a step of reacting the second mixed solution to form a shell containing chitosan coated on the core.
[0020] In addition, the second mixed solution of step (b-2) can be reacted at a pH of 3.5 to 4.5.
[0021] In addition, the chitosan may include chitosan nanowhiskers.
[0022] In addition, the method for manufacturing the cellulose bead composite may further include a step (a') of manufacturing the cellulose beads before step (a).
[0023] Additionally, the above step (a') may include: (a'-1) a step of preparing a first mixed solution comprising a cellulose derivative, an emulsifier, and an organic solvent; (a'-2) a step of preparing a second mixed solution comprising a bioactive substance, an emulsifier, and water; (a'-3) a step of performing a membrane emulsification process by applying shear force by causing the first mixed solution and the second mixed solution to flow perpendicularly to each other; (a'-4) a step of coagulating the cellulose derivative emulsion prepared through the membrane emulsification process; and (a'-5) a step of producing cellulose beads by diacetylating the coagulated cellulose acetate.
[0024] In addition, the cellulose derivative may include one or more selected from the group consisting of cellulose acetate (CA), cellulose propionate (CP), cellulose acetate phthalate (CAP), ethylcellulose (EC), methylcellulose (MC), carboxymethylcellulose, hydroxyethylcellulose (HEC), and sodium carboxymethylcellulose (NaCMC).
[0025] In addition, the size of the cellulose bead composite may be 500 nm to 5 μm.
[0026] In addition, the cellulose bead composite may contain pores. Effects of the invention
[0027] The present invention can provide an eco-friendly core-shell structured porous cellulose bead composite using cellulose and a method for manufacturing the same.
[0028] In addition, the present invention can provide a porous cellulose bead composite having a core-shell structure comprising a bioactive substance and chitosan, and a method for manufacturing the same.
[0029] In addition, the present invention can provide a porous cellulose bead composite with a core-shell structure that improves drug stability and sustained drug release performance, and a method for manufacturing the same. Brief explanation of the drawing
[0030] These drawings are for reference to explain exemplary embodiments of the present invention, and therefore, the technical concept of the present invention should not be interpreted as being limited to the attached drawings. Figure 1 is a flowchart of the method for manufacturing a cellulose bead composite of the present invention. Figure 2 is a schematic diagram of a cross-flow membrane emulsion. Figure 3 is an optical microscope image of ac, cellulose acetate, and df, cellulose beads. Figure 4 is the FT-IR spectrum of cellulose acetate beads and cellulose beads. Figure 5 is a diagram showing the pH measurement results of cellulose acetate beads and cellulose beads. Figure 6 is a diagram showing the cytotoxicity of cellulose acetate beads and cellulose beads. Figure 7 is a diagram showing the results of a microcompression test of cellulose acetate beads and cellulose beads. Figure 8 is a diagram showing (a) nitrogen adsorption-desorption isotherms and (b) pore volume distribution of synthesized beads. Figure 9 is the FTIR spectrum of Vitamin C, chitosan nanowhiskers, Preparation Example 2, Comparative Example 1, and Comparative Example 2. Figure 10 is an SEM image of Example 1. Figure 11 shows the release of Vitamin C of Example 1 over time under pH conditions of 4.0, 5.5, and 7.4. Figure 12 shows the ultraviolet-visible (UV-Vis) absorbance spectrum (265 nm) before and after loading vitamin C onto cellulose beads for 24 hours. Specific details for implementing the invention
[0031] Hereinafter, embodiments of the present invention will be described in detail with reference to the attached drawings so that those skilled in the art can easily implement the present invention.
[0032] However, the following description is not intended to limit the present invention to specific embodiments, and detailed descriptions of related prior art are omitted if it is determined that such detailed descriptions could obscure the essence of the present invention.
[0033] The terms used herein are merely for describing specific embodiments and are not intended to limit the invention. The singular expression includes the plural expression unless the context clearly indicates otherwise. In this application, terms such as “comprising” or “having” are intended to specify the presence of the features, numbers, steps, actions, components, or combinations thereof described in the specification, and should be understood as not precluding the existence or addition of one or more other features, numbers, steps, actions, components, or combinations thereof.
[0034] Additionally, terms including ordinal numbers, such as "first," "second," etc., used below may be used to describe various components, but said components are not limited by said terms. These terms are used solely for the purpose of distinguishing one component from another. For example, without departing from the scope of the present invention, the first component may be named the second component, and similarly, the second component may be named the first component.
[0035] Furthermore, when it is stated that a component is "formed" or "laminated" on another component, it should be understood that while it may be formed or laminated by being directly attached to the entire surface or one surface of the other component, there may also be other components present in between.
[0036] Hereinafter, a method for manufacturing a porous cellulose bead composite having a core-shell structure including additives and a coating agent will be described in detail. However, this is presented as an example and is not intended to limit the present invention, and the present invention is defined only by the scope of the claims set forth below.
[0037] According to one aspect of the present invention, a cellulose bead composite is provided comprising: a core comprising a porous cellulose bead having pores and a bioactive substance supported on the porous cellulose bead; and a shell comprising chitosan coated on the core.
[0038] In addition, the size of the porous cellulose beads may be 500 nm to 5 μm, preferably 1 to 3 μm. Here, if the size of the porous cellulose beads is less than 500 nm, particle aggregation and reduced stability occur during the manufacturing process, and it is difficult to form a sufficient pore structure inside the beads, which reduces the loaded amount of drug, so it is undesirable; and if it exceeds 5 μm, it is undesirable because it increases the feeling of strangeness when applied to the skin, the release rate of the drug may become excessively slow, and the dispersion stability within the cosmetic formulation may be reduced.
[0039] In addition, the specific surface area of the porous cellulose beads is 5 to 100 m² 2 / g, preferably 10 to 40 m 2 It can be / g. Here, the specific surface area of the porous cellulose beads is 5 m 2 If it is less than / g, the drug loading is insufficient, making it difficult to achieve efficacy and impairing release control, so it is undesirable, and 100 m 2 If it exceeds / g, the pore structure becomes excessively developed, leading to rapid initial release of the drug and potentially reducing structural stability, which is undesirable.
[0040] In addition, the specific pore volume of the porous cellulose beads is 0.05 to 1.00 cm 3 / g, preferably 0.1 to 0.50 cm 3 It can be / g. Here, the pore volume of the porous cellulose beads is 0.05 cm³ 3 If it is less than / g, pores are not sufficiently formed, which reduces the loading capacity of drugs or physiologically active substances and impairs the release control function, so it is undesirable, and 1.00 cm 3If it exceeds / g, the pores become excessively large, which lowers structural stability and is undesirable as physical deformation or collapse of the beads may occur due to external impact or flow environment.
[0041] In addition, the above-mentioned bioactive substance may include one or more selected from the group consisting of vitamin C, vitamin A, vitamin E, niacinamide, salicylic acid, kojic acid, alpha-lipoic acid, ellagic acid, resveratrol, docohexaenoic acid (DHA), eicosapentaenoic acid (EPA), linoleic acid (LA), glutathione, caffeine, tranexamic acid, azelaic acid, and hyaluronic acid.
[0042] In addition, the above-mentioned bioactive substance may be supported on one or more selected from the group consisting of the surface of the porous cellulose and the pores of the porous cellulose.
[0043] In addition, the chitosan may include chitosan nanowhiskers.
[0044] In addition, the cellulose bead complex can release the bioactive substance to the outside of the cellulose bead complex over time.
[0045] According to another aspect of the present invention, a method for manufacturing a cellulose bead composite is provided, comprising: (a) reacting a first mixed solution comprising porous cellulose beads having pores and a bioactive substance to produce a core comprising said bioactive substance and a bioactive substance supported on said porous cellulose beads; and (b) reacting the core with a second mixed solution comprising chitosan to form a shell comprising chitosan coated on said core.
[0046] Additionally, the above step (a) may include (a-1) a step of preparing a first mixed solution comprising porous cellulose beads having pores and a bioactive substance; and (a-2) a step of reacting the first mixed solution to prepare a core comprising the bioactive substance and the bioactive substance supported on the porous cellulose beads.
[0047] In addition, the first mixed solution of step (a-2) can be reacted at a pH of 1.5 to 2.5.
[0048] In addition, the above-mentioned bioactive substance may include one or more selected from the group consisting of vitamin C, vitamin A, vitamin E, niacinamide, salicylic acid, kojic acid, alpha-lipoic acid, ellagic acid, resveratrol, docohexaenoic acid (DHA), eicosapentaenoic acid (EPA), linoleic acid (LA), glutathione, caffeine, tranexamic acid, azelaic acid, and hyaluronic acid.
[0049] Additionally, the above step (b) may include (b-1) a step of preparing a second mixed solution containing the core and chitosan; and (b-2) a step of reacting the second mixed solution to form a shell containing chitosan coated on the core.
[0050] In addition, the second mixed solution of step (b-2) can be reacted at a pH of 3.5 to 4.5.
[0051] In addition, the chitosan may include chitosan nanowhiskers.
[0052] In addition, the method for manufacturing the cellulose bead composite may further include a step (a') of manufacturing the cellulose beads before step (a).
[0053] Additionally, the above step (a') may include: (a'-1) a step of preparing a first mixed solution comprising a cellulose derivative, an emulsifier, and an organic solvent; (a'-2) a step of preparing a second mixed solution comprising a bioactive substance, an emulsifier, and water; (a'-3) a step of performing a membrane emulsification process by applying shear force by causing the first mixed solution and the second mixed solution to flow perpendicularly to each other; (a'-4) a step of coagulating the cellulose derivative emulsion prepared through the membrane emulsification process; and (a'-5) a step of producing cellulose beads by diacetylating the coagulated cellulose acetate.
[0054] In addition, the cellulose derivative may include one or more selected from the group consisting of cellulose acetate (CA), cellulose propionate (CP), cellulose acetate phthalate (CAP), ethylcellulose (EC), methylcellulose (MC), carboxymethylcellulose, hydroxyethylcellulose (HEC), and sodium carboxymethylcellulose (NaCMC).
[0055] In addition, the size of the cellulose bead composite may be 500 nm to 5 μm. Here, if the size of the cellulose bead composite is less than 500 nm, particle aggregation and reduced stability occur during the manufacturing process, and it is difficult to form a sufficient pore structure inside the bead, which reduces the loaded amount of drug, so it is undesirable; and if it exceeds 5 μm, it is undesirable because it causes a greater sense of strangeness when applied to the skin, the release rate of the drug may become excessively slow, and dispersion stability within the cosmetic formulation may be reduced.
[0056] In addition, the cellulose bead composite may contain pores.
[0057] The present invention will be explained in more detail below with reference to examples. However, this is for illustrative purposes only and does not limit the scope of the present invention.
[0058] [Example]
[0059] substance
[0060] Cellulose acetate in powder form (number average molecular weight (Mn) by GPC ~30,000, density of 1.3 g / mL at 25°C) was purchased from Sigma-Aldrich. A hydrophilic membrane composed of polytetrafluoroethylene (PTFE) (0.45 μm pore size, diameter Φ47 mm, sterile) was Wisd TMSunflower oil was purchased from Nobrand (Seoul, South Korea). Dimethyl sulfoxide (DMSO, purity > 99%), hexane (≥ 97%), Span 80, Tween 80, and NaOH (98.0%) were purchased from Sigma-Aldrich. Pure ethanol (> 99.9%) and acetone (> 99.9%) were purchased from Daejeong. ODTES (> 85.0% purity) was purchased from Tokyo Chemical Industry (TCI) Co., Ltd. Dimethylsiloxane copolymer (viscosity: 25-35 cSt, MW 1900-2000 g / mol) was purchased from Gelest. Polymethylsilsesquioxane (KSP-101, ShinEtsu, Japan) and vinyl dimethicone / methicone silsesquioxane (vinyl dimethicone, KMP 590, ShinEtsu, Japan) were purchased from Korea Cosmetics Co., Ltd. C2C12 cells (CRL-1772) and 10% fetal bovine serum (FBS, Cat. No. 30-2020) were purchased from the American Type Culture Collection (ATCC, USA). Dulbecco's Modified Eagle medium (DMEM, Cat. No. SH30243) and penicillin / streptomycin (Cat. No. SV30010) were purchased from HyClone (Logan, Utah, USA). Cell Count Kit-8 (CCK-8) was purchased from Dojindo Laboratories (Kumamoto, Japan). Nickel(II) sulfate (NiSO4) was purchased from Sigma-Aldrich (USA).
[0061] Preparation Example 1: Cellulose acetate beads
[0062] Figure 2 is a schematic diagram showing the process of preparing cellulose acetate beads using a cross-flow membrane emulsification method. Referring to Figure 2, membrane emulsification requires two phases: a dispersed phase and a continuous phase, and in this experiment, cellulose acetate was used as the dispersed phase. A homogeneous solution was prepared by dissolving cellulose acetate (16 wt%) in 50 mL of DMSO by continuous stirring at 60 °C, and Tween 80 (20 mL) was added for emulsion stability. Sunflower oil (300 mL) was used as the continuous phase, and Span 80 (20 mL) was added together to promote emulsification.
[0063] The continuous phase was set to flow along the membrane surface at a constant flow rate of 750 mL / min using a microgear pump (WT3000-1FA, Longer Precision Pump Co. Ltd.). Using nitrogen pressure, the dispersed phase was injected into the continuous phase through a hydrophilic membrane with a pore size of 0.01 μm, thereby forming a stable emulsion. The formed emulsion was immediately pumped into 300 mL of ethanol to solidify into beads, which were subsequently washed with ethanol and filtered. The filtered cellulose acetate beads were dispersed in hexane and air-dried until the solvent completely evaporated to prevent aggregation.
[0064] Preparation Example 2: Porous cellulose beads
[0065] The cellulose acetate beads prepared in Preparation Example 1 above were immersed in a 0.05 M NaOH aqueous solution and subjected to a deacetylation process at room temperature for 24 hours. Repeating this process twice further promoted the formation of pores in the beads. After each step, filtration was performed using a sterile hydrophilic membrane with 0.45 μm pores, and the beads were subsequently dispersed in hexane and air-dried. Through this process, cellulose beads with a porous structure were obtained.
[0066] Example 1: Vitamin C-loaded, chitosan-coated porous cellulose beads
[0067] Figure 1 is a flowchart illustrating the manufacturing process of the porous cellulose bead composite of the present invention. Referring to Figure 1, 0.5 g of the porous cellulose beads prepared in Preparation Example 2 were immersed in 20 mL of an aqueous solution containing 1 g of vitamin C dissolved therein, and vitamin C was loaded by stirring at 250 rpm at 25°C for 24 hours. This process was performed under light-blocking conditions to prevent oxidation of vitamin C. After the reaction, the beads were allowed to stand until they precipitated, after which the supernatant was removed, leaving approximately 10 mL of residual solution. Subsequently, the beads were washed with ethanol, dispersed in nucleic acid, and then filtered and air-dried to produce porous cellulose beads loaded with vitamin C.
[0068] The above-mentioned porous cellulose beads loaded with vitamin C are Kim, HJ, Bae, JH, & Eom, Y. (2025). Creating ultra-strong and recyclable green plastics from marine-sourced alginate-chitosan nanowhisker nanocomposites for controlled release urea fertilizer. Carbohydrate Polymers , 34720 g of a chitosan nanowhisker (hereinafter CSW) suspension prepared according to the method of 122745 was mixed. The CSW suspension was prepared at a concentration of 1.6 wt%, and the chitosan nanowhiskers dispersed in ultrapure water were stirred to form a uniform suspension. About 15 mL of ethanol was dropwise added to the mixed solution to adjust the pH to about 4.0, and then the mixture was stirred at 25°C and 250 rpm for 3 hours under electrostatic adsorption conditions so that the positively charged chitosan nanowhiskers were uniformly adsorbed onto the surface of negatively charged cellulose beads by electrostatic attraction. After the coating was completed, the bead surface was washed with approximately 200 mL of ethanol to remove unreacted chitosan and impurities, filtered, dispersed in nucleic acid, and air-dried for 24 hours to produce chitosan-coated vitamin C-supported cellulose beads.
[0069] Comparative Example 1: Porous cellulose beads loaded with vitamin C
[0070] 0.5 g of the porous cellulose beads prepared above were immersed in 20 mL of an aqueous solution containing 1 g of vitamin C dissolved therein, and vitamin C was loaded by stirring at 250 rpm at 25°C for 24 hours. This process was carried out under light-blocking conditions to prevent oxidation of vitamin C. After the reaction, the beads were allowed to stand until they precipitated, after which the supernatant was removed, leaving approximately 10 mL of residual solution. Subsequently, the beads were washed with ethanol, dispersed in nucleic acid, and then filtered and air-dried to produce porous cellulose beads loaded with vitamin C.
[0071] Comparative Example 2: Chitosan-coated porous cellulose beads
[0072] 0.5 g of the porous cellulose beads obtained in Preparation Example 2 prepared above was mixed with 20 g of a 1.6 wt% chitosan nanowhisker (hereinafter CSW) suspension, and about 15 mL of ethanol was added dropwise to adjust the pH of the mixture to about 4.0. The adjusted mixture was stirred at 25°C and 250 rpm for 3 hours under electrostatic adsorption conditions to allow positively charged chitosan whiskers to be adsorbed onto the surface of negatively charged porous cellulose beads by electrostatic attraction. After coating was completed, the mixture was washed with about 200 mL of ethanol to remove unreacted chitosan and impurities, filtered, dispersed in nucleic acid, and dried in air for 24 hours to produce chitosan-coated porous cellulose beads.
[0073] [Test Example]
[0074] Test Example 1: Comparative Morphological Analysis of Cellulose Microbeads
[0075] The morphology of the produced beads was comprehensively investigated by microscopy as presented in Fig. 3. Fig. 3 shows optical microscope images of cellulose acetate beads (ac) and cellulose beads (df). Referring to Fig. 3 provides preliminary insights into the approximate pair size and shape of the beads. These images demonstrate that, regardless of the type of cellulose, most beads exhibit a well-defined spherical structure, indicating a successful emulsification and solidification process. Scanning electron microscopy (SEM) analysis was performed to better understand the surface morphology. The SEM images show that both cellulose acetate (Fig. 3b) and cellulose (Fig. 3e) beads remain spherical and maintain a very similar appearance, suggesting that the deacetylation process did not significantly alter the overall shape of the beads. The size distribution of the cellulose beads was further verified by laser diffraction analysis. This analysis ensures the accuracy and reproducibility of the size distribution data by measuring bead sizes in detail across a wide range of samples. The size distribution analysis revealed a slight increase in particle size with each chemical modification. Cellulose acetate beads exhibited the smallest size of 5.78 ± 1.224 μm. After deacetylation, the size of the cellulose beads increased to 6.97 ± 1.56 μm, which may be due to structural rearrangement and expansion during deacetylation. Further modification using ODTES increased the size to 7.96 ± 1.80 μm, attributed to the hydrophobic silane chains of ODTES implanted on the cellulose surface, resulting in slight aggregation or clustering of the particles. These changes in size suggest that the chemical treatment had a slight effect on the particle surface, leading to limiting growth while maintaining uniformity. These results are based on an average of five measurements and showed a relatively narrow size distribution, confirming consistent bead formation throughout the manufacturing process. This comprehensive analysis confirmed that bead formation is well-established and that the bead shape remained consistent even after deacetylation.Consistency in bead size and shape, along with observed differences in surface texture, highlights the successful transformation from cellulose acetate to cellulose beads, maintaining structural integrity and uniformity throughout the process. However, significant differences in surface characteristics are observed between the two bead types. While the surface of the cellulose acetate beads appeared smooth and uniform (Fig. 3c), the cellulose beads exhibited a rough and uneven texture (Fig. 3f), and the cellulose beads displayed an apparent porous structure. These changes in surface morphology can be attributed to the acetylation process, which involves the removal of acetyl groups and their replacement with hydroxyl groups, introducing surface roughness and resulting in a more irregular and porous surface.
[0076] Test Example 2: Spectroscopic analysis of chemical modification of cellulose microbeads
[0077] Figure 4 shows the FT-IR spectra of cellulose acetate beads and cellulose beads. Referring to Figure 4, the chemical structure of the produced beads was investigated using FT-IR spectroscopy. FTIR analysis provides important information regarding the functional groups present in the beads, which is essential for understanding the chemical changes occurring during the deacetylation process. A comparison of the FT-IR spectra of the cellulose acetate beads and cellulose beads revealed significant changes, particularly regarding the characteristic peaks of the acetyl groups. Specifically, the 1731 cm⁻¹ peak corresponds to the stretching vibrational mode of the C=O bond in the ester group, the CH bending vibration of the CH₃ group, and the asymmetric stretching of the CO bond. -1 , 1357cm -1 and 1217cm -1 The intense signals were significantly altered or vanished after deacetylation, respectively, indicating the effective removal of acetyl groups and thus confirming the successful conversion of cellulose acetate to cellulose. Furthermore, the FT-IR spectrum revealed the emergence of a new characteristic band associated with the cellulose structure at approximately 3300–3400 cm⁻¹. -1The broad bands appearing at 1027 cm⁻¹ are not distinct in cellulose acetate and represent the characteristics of hydroxyl (-OH) groups indicating the cellulose backbone; this is a characteristic feature of cellulose that contributes to its intrinsic physical properties. -1 The band is a characteristic of the COC bond in the anhydrous glucose unit of the cellulose backbone, further confirming that cellulose acetate has been successfully converted into cellulose.
[0078] Through this comprehensive analysis combining microscopy and FT-IR spectroscopy, the morphological and chemical functional relationships of the beads were verified. Morphological analysis confirmed the structural integrity and uniformity of the beads, while FT-IR analysis provided decisive evidence of chemical changes and functional group trans formation that occurred during the deacetylation and effective introduction of new functional groups, confirming the successful modification and subsequent functionalization of the cellulose beads. As a result, cellulose beads with distinct chemical functionality were formed.
[0079] Test Example 3: Evaluation of pH stability, purity, and biocompatibility of synthetic cellulose microbeads
[0080] The primary advantage of cellulose beads is their biocompatibility, as they are naturally derived from basic plant components. Due to this inherent biocompatibility, cellulose is a suitable candidate for use in cosmetics, particularly those applied directly to the human skin. The pH value of ingredients is a critical factor when formulating cosmetics, as it must match the skin's natural pH balance. Cosmetics generally require a pH range of 3 to 9 to ensure a gentle and non-irritating application to the skin.
[0081] Figure 5 shows the pH measurement results of cellulose acetate beads and cellulose beads. Referring to Figure 5, pH values were investigated to determine whether cellulose acetate beads and cellulose beads are suitable for cosmetic applications. According to the results, the cellulose beads maintained a nearly neutral pH of 7. This neutrality indicates that the formulation process is simplified and the potential for skin irritation is reduced, as the overall pH needs to be adjusted minimally when incorporating cellulose beads into cosmetic formulations. Furthermore, consistency was highlighted as the pH of the cellulose beads remained stable at various concentrations. Additionally, EDS analysis confirmed that no impurities, such as heavy metals, were introduced during the emulsification process used to synthesize the cellulose beads. For further verification, ICP-MS was performed to evaluate whether the cellulose acetate beads and cellulose beads were free of heavy metal impurities. The analysis targeted nine heavy metals: Ag, Al, Pb, Cd, Hg, Cu, As, Ba, and Sb. The results confirmed that the concentrations of all nine metals were below the detection limit, with a concentration of 0 ppm in all samples. This was an expected result, as no metals were used during the sample preparation or modification process. Because the micro beads are free of heavy metal impurities and contaminants, they are safe and particularly suitable for sensitive applications where strict control of purity and safety is critical, such as cosmetics and pharmaceuticals. Additionally, the biocompatibility of the cellulose micro beads was verified, and in vitro cytotoxicity was evaluated. Figure 6 illustrates the cytotoxicity of cellulose acetate beads and cellulose beads. Referring to Figure 6, the untreated state and the NiSO4-treated state were used as negative and positive controls, respectively. The samples (cellulose acetate and cellulose beads) were prepared by diluting them tenfold in cell culture medium from 100 to 0.001 μg / mL. Compared to the negative control, most of the cells in the positive control were dead, indicating that the analysis was performed successfully.In addition, the samples showed no cytotoxicity whatsoever, and cells grew well without significant effects, particularly at the highest concentration of 100 µg / mL. In summary, the biocompatibility, neutral pH, and absence of impurities of the synthetic cellulose beads demonstrate that they are suitable and safe for use in a wide range of cosmetic applications.
[0082] Test Example 4: Analysis of Compressive Strength of Cellulose Microbeads
[0083] Microbeads used in the cosmetics industry require adequate mechanical strength to ensure functionality and durability in products such as scrubs and cleansers. Compressive strength, which measures a material's ability to withstand loads that compress or reduce its size, is particularly important for these applications. Figure 7 illustrates the results of microcompression tests on cellulose acetate beads and cellulose beads. Referring to Figure 7, the stress applied to the material is measured and the corresponding displacement is tracked, providing insight into the material's mechanical properties. The compressive strength of the material is determined by identifying the point where the stress increases sharply, which indicates significant deformation in the particle structure. Stress-displacement curves were plotted for each bead type, and compressive strength was identified at the point where the slope of the stress curve increased significantly.
[0084] Table 1 below shows the compressive strength of cellulose acetate beads and cellulose beads. Referring to Table 1, the synthesized cellulose acetate beads exhibited a strength of 15.18 ± 0.22 MPa, while the cellulose beads showed a strength of 5.75 ± 0.52 MPa. Additionally, commercially available micro beads, such as polymethylsilsesquioxane and vinyl dimethicone, commonly used in cosmetics, were evaluated. Polymethylsilsesquioxane exhibited a significantly high compressive strength of 337.201 ± 20.094 MPa, whereas vinyl dimethicone showed a compressive strength of 6.21 ± 1.193 MPa, similar to that of the cellulose micro beads. These results indicate that micro beads used in cosmetics do not require excessively high compressive strength due to their wide range of applications. Since vinyl dimethicone is widely used in cosmetic formulations despite its lower compressive strength, cellulose beads, which exhibit similar mechanical properties, are practically suitable for use in similar cosmetics. In addition, in typical usage scenarios, the pressure applied by human grip strength is 1.49 MPa on average for men and 0.94 MPa for women, which is significantly lower than the compressive strength of cellulose beads.
[0085] Microbeads Compressive strength (MPa) 1st 2nd 3rd 4th 5th Error Result Example 1 Cellulose acetate 15.532 15.019 15.134 14.836 15.379 0.2204 15.18 ± 0.22 Example 2 Cellulose 6.549 5.164 6.052 5.958 5.027 0.5236 5.75 ± 0.52
[0086] Another important point is that the surface modification process affects the mechanical properties of micro beads. In particular, a comparison of the stress-displacement curves of cellulose acetate and cellulose beads revealed a noticeable difference. Cellulose acetate beads exhibit more ductile behavior, as the slope of the stress curve does not change abruptly. This is because the polymer chains of cellulose acetate have an amorphous structure, allowing for greater flexibility and deformation under stress. On the other hand, cellulose beads exhibit more brittle characteristics, as the slope of the stress curve changes abruptly. This brittleness occurs during the deacetylation process, which increases internal hydrogen bonding to induce crystallinity within the cellulose structure, resulting in a harder material. The crystallinity of cellulose was confirmed through XRD analysis. This result is supported by the fact that crystallinity is more pronounced in cellulose than in cellulose acetate. The peaks observed at 12.1°, 20.1°, and 22.0° in the XRD pattern correspond to (1-10), (110), and (020) reflections, respectively, with d-spacings of 7.19 Å, 4.42 Å, and 4.06 Å, respectively. This is characteristic of cellulose II. This is consistent with the fact that the synthesized cellulose originates through deacetylation, which is a transition from cellulose acetate to cellulose II. Deacetylation causes the rearrangement of polymer chains, creating voids or pores within the structure. These pores are clearly visible in the SEM images, demonstrating the porous surface morphology of the cellulose beads. Since these pores impair the integrity of the material, they may contribute to a decrease in mechanical strength.
[0087] Test Example 5: Investigation of the physical structure of cellulose microbeads
[0088] The compressive strength results were further supported by BET surface area analysis. Figure 8 shows (a) the nitrogen adsorption-desorption isotherm and (b) the pore volume distribution of the synthesized beads, and Table 2 below shows the surface area and pore volume of the cellulose acetate beads and cellulose beads at the N2 isotherm. Referring to Figure 8 and Table 2, the nitrogen adsorption isotherm of the BET surface area and pore volume distribution for each bead type can be determined. As expected, the cellulose beads were 24.99 m 2 It showed a larger surface area at / g, followed by cellulose acetate beads at 15.56m 2 They exhibited a surface area of / g. Pore volume also showed noticeable differences between the beads. The cellulose beads were 0.163 cm. 3 It exhibited the highest pore volume at / g, consistent with the observed higher surface area and porous structure. The cellulose acetate beads were 0.158 cm² 3 It showed a slightly lower pore volume of / g.
[0089] Microbead Surface area(m 2 g -1 ) Pore volume(cm 3 g -1 ) Example 1 Cellulose acetate 15.56 0.158 Example 2 Cellulose 24.99 0.163
[0090] In terms of pore size distribution, cellulose beads exhibited relatively small pores, whereas cellulose acetate beads displayed larger pores. BET surface area and pore volume analysis confirmed the porosity of the synthesized beads, providing a deeper understanding of their structural characteristics. Thus, BET analysis offers a more in-depth understanding of the bead structure. These results highlight the suitability of modified cellulose beads for cosmetic applications where both mechanical strength and structural integrity are essential.
[0091] Test Example 6: FTIR Spectrum Analysis
[0092] Figure 9 shows the FTIR spectra of Vitamin C, chitosan nanowhiskers, Preparation Example 2, Comparative Example 1, and Comparative Example 2. Referring to Figure 9, the Cellulose Beads of Preparation Example 2 and the Uncoated DDS Beads of Comparative Example 1 are at 1000–1200 cm⁻¹. - In region ¹, the COC vibration peak of cellulose is observed, and in the sample loaded with Vitamin C, it can be seen that the characteristic peak of Vitamin C partially overlaps with this.
[0093] In addition, for the CSW Coated DDS Beads sample, which is Comparative Example 2, 3677 cm - ¹(OH), 1404 cm - ¹(CH), 1227 cm - A distinct peak is observed near ¹(NH), which is attributed to the characteristic peak of the chitosan whisker and indicates that chitosan has been successfully coated on the surface of the cellulose beads.
[0094] Therefore, the FTIR analysis results prove that both the loading of vitamin C and the surface coating of the chitosan whiskers were chemically effective.
[0095] Test Example 7: SEM Image Analysis
[0096] Figure 10 is an SEM image of Example 1. Referring to Figure 10, it can be seen that the cellulose beads have a spherical porous structure and that chitosan whiskers are coated on the surface in a layered structure. This confirms that the surface coating of chitosan whiskers was successfully achieved.
[0097] Test Example 8: UV-Vis Spectrum Analysis
[0098] Figure 11 shows the release of Vitamin C of Example 1 over time under pH conditions of 4.0, 5.5, and 7.4, and Figure 12 shows the ultraviolet-visible (UV-Vis) absorbance spectrum (265 nm) before and after loading Vitamin C onto cellulose beads for 24 hours.
[0099] Referring to Figure 11, the highest release of vitamin C was 20.78% at pH 5.5, while the release amounts were 12.73% at pH 7.4 and 8.44% at pH 4.0, which were relatively lower than those at pH 5.5. This indicates that vitamin C release is affected by pH and is most effectively released at pH 5.5.
[0100] In addition, referring to Figure 12, it is confirmed that the absorbance at approximately 265 nm in the spectrum after loading has decreased significantly compared to before loading, which means that the concentration of vitamin C in the solution has decreased. This decrease in absorbance indicates that vitamin C was effectively adsorbed onto the cellulose beads and that the loading was successful. In other words, the change in absorbance at 265 nm, which is the characteristic absorption wavelength of vitamin C, can be interpreted as an indicator that can quantitatively evaluate the adsorption of vitamin C and the loading efficiency.
[0101] Although preferred embodiments of the present invention have been described above, those skilled in the art may modify and change the present invention in various ways by adding, changing, deleting, or adding components, etc., without departing from the spirit of the present invention as described in the claims, and such modifications and changes shall also be deemed to be included within the scope of the rights of the present invention. For example, each component described as a single unit may be implemented in a distributed manner, and components described as distributed may likewise be implemented in a combined form. The scope of the present invention is defined by the claims set forth below rather than by the detailed description above, and all modifications or variations derived from the meaning and scope of the claims and equivalent concepts thereof should be interpreted as being included within the scope of the present invention.
Claims
Claim 1 A cellulose bead composite comprising: a core comprising porous cellulose beads having pores and a bioactive substance supported on said porous cellulose beads; and a shell comprising chitosan coated on said core. Claim 2 A cellulose bead composite according to claim 1, characterized in that the size of the porous cellulose beads is 1 to 50 μm. Claim 3 In claim 1, the specific surface area of the porous cellulose beads is 5 to 100 m² 2 A cellulose bead complex characterized by having a weight of / g. Claim 4 In claim 1, the specific pore volume of the porous cellulose beads is 0.05 to 1.00 cm 3 A cellulose bead complex characterized by having a weight of / g. Claim 5 A cellulose bead complex according to claim 1, characterized in that the physiologically active substance comprises one or more selected from the group consisting of vitamin C, vitamin A, vitamin E, niacinamide, salicylic acid, kojic acid, alpha-lipoic acid, ellagic acid, resveratrol, docohexaenoic acid (DHA), eicosapentaenoic acid (EPA), linoleic acid (LA), glutathione, caffeine, tranexamic acid, azelaic acid, and hyaluronic acid. Claim 6 A cellulose bead composite according to claim 1, characterized in that the physiologically active substance is supported on one or more selected from the group consisting of the surface of the porous cellulose and the pores of the porous cellulose. Claim 7 A cellulose bead composite according to claim 1, characterized in that the chitosan comprises chitosan nanowhiskers. Claim 8 A cellulose bead complex according to claim 1, characterized in that the cellulose bead complex releases the physiologically active substance to the outside of the cellulose bead complex over time. Claim 9 (a) a step of preparing a core comprising the bioactive substance and the bioactive substance supported on the porous cellulose beads by reacting a first mixed solution comprising porous cellulose beads having pores and a bioactive substance; and (b) a step of forming a shell comprising chitosan coated on the core by reacting the core with a second mixed solution comprising chitosan; a method for preparing a cellulose bead composite comprising: (a) a step of preparing a core comprising the bioactive substance and the bioactive substance supported on the porous cellulose beads by reacting the core with a second mixed solution comprising chitosan. Claim 10 A method for manufacturing a cellulose bead composite according to claim 9, wherein step (a) comprises: (a-1) a step of preparing a first mixed solution comprising porous cellulose beads having pores and a bioactive substance; and (a-2) a step of reacting the first mixed solution to prepare a core comprising the bioactive substance and the bioactive substance supported on the porous cellulose beads. Claim 11 A method for manufacturing a cellulose bead composite according to claim 10, characterized by reacting the first mixed solution of step (a-2) at a pH of 1.5 to 2.
5. Claim 12 A method for manufacturing a cellulose bead complex according to claim 9, wherein the above-mentioned physiologically active substance comprises one or more selected from the group consisting of vitamin C, vitamin A, vitamin E, niacinamide, salicylic acid, kojic acid, alpha-lipoic acid, ellagic acid, resveratrol, docohexaenoic acid (DHA), eicosapentaenoic acid (EPA), linoleic acid (LA), glutathione, caffeine, tranexamic acid, azelaic acid, and hyaluronic acid. Claim 13 A method for manufacturing a cellulose bead composite according to claim 9, wherein step (b) comprises: (b-1) a step of preparing a second mixed solution containing the core and chitosan; and (b-2) a step of reacting the second mixed solution to form a shell containing chitosan coated on the core. Claim 14 A method for manufacturing a cellulose bead composite according to claim 13, characterized by reacting the second mixed solution of step (b-2) at a pH of 3.5 to 4.
5. Claim 15 A method for manufacturing a cellulose bead composite according to claim 9, characterized in that the chitosan comprises chitosan nanowhiskers. Claim 16 A method for manufacturing a cellulose bead composite according to claim 9, characterized in that the method for manufacturing the cellulose bead composite further comprises the step of manufacturing the cellulose beads (a') prior to step (a). Claim 17 A method for manufacturing a cellulose bead composite according to claim 9, wherein step (a') comprises: (a'-1) a step of preparing a first mixed solution comprising a cellulose derivative, an emulsifier, and an organic solvent; (a'-2) a step of preparing a second mixed solution comprising a physiologically active substance, an emulsifier, and water; (a'-3) a step of performing a membrane emulsification process by applying shear force to flow the first mixed solution and the second mixed solution perpendicular to each other; (a'-4) a step of coagulating the cellulose derivative emulsion prepared through the membrane emulsification process; and (a'-5) a step of producing cellulose beads by diacetylating the coagulated cellulose acetate. Claim 18 A method for manufacturing a cellulose bead composite according to claim 17, characterized in that the cellulose derivative comprises one or more selected from the group consisting of cellulose acetate (CA), cellulose propionate (CP), cellulose acetate phthalate (CAP), ethylcellulose (EC), methylcellulose (MC), carboxymethylcellulose, hydroxyethylcellulose (HEC), and sodium carboxymethylcellulose (NaCMC). Claim 19 A method for manufacturing a cellulose bead composite according to claim 15, characterized in that the size of the cellulose bead composite is 500 nm to 5 μm. Claim 20 A method for manufacturing a cellulose bead composite according to claim 15, characterized in that the cellulose bead composite comprises pores.